Effects of cannabinoid CB1 receptor activation upon exercise-induced insulin stimulated glucose uptake in human primary skeletal muscle myotubes - Mohd Noor, Mohd Fadly; Bennett, Andrew J.; Tsintzas, Kostas (2016)
Endocannabinoid system (ECS) plays an important role in the regulation of energy balance and metabolism. Studies showed that the activation of cannabinoid receptor type-1 (CB1) may lead to increase in food intake, weight gain, obesity and impairment in glucose tolerance. The aim of this study is to examine the effects of CB1 activation upon exercise-induced insulin stimulated glucose uptake in human primary skeletal muscle myotubes. We have developed a contractile myotubes model using electrical pulse stimulation (EPS) which demonstrates elevation in glucose transporter 4 (GLUT4), together with increased in insulin stimulated glucose uptake by the cells after EPS. Activation of CB1 by Arachidonoyl 2'-Chloroethylamide (ACEA) resulted in significant reduction in insulin stimulated glucose uptake and this effect were reverted with pre-treatment with CB1 antagonist: Rimonabant (RIM). Protein expression by western blotting revealed the activity of Akt/protein kinase B in insulin signalling pathway was inhibited by ACEA and this may suggest the mechanism of the inhibition of glucose uptake. In conclusion, activation of CB1 by ACEA inhibit exercise-induced insulin stimulated glucose uptake in human primary skeletal muscle myotubes via inhibition of Akt/protein kinase B activity and the effects was blunted by pre-treatment with RIM.